RMS Pictorial Scale (RMS-PS): An innovative scale for the assessment of child's dental anxiety - R M Shetty; M Khandelwal; S Rath (Wolters Kluwer Medknow Publications, 2015)
Background: Dental anxiety assessment for young children is as important as performing their treatment. Appropriate knowledge of patient's anxiety boosts confidence and will help us to review potential management options specific to every child. Aim: This study aimed to validate (RMS) Pictorial Scale (RMS-PS) and to compare it with Venham Picture Test (VPT) and Facial image scale (FIS) in measuring dental anxiety for young children during their first dental visit. Materials and Methods: A total of 102 healthy children aged between 4 and 14 years during their first dental visit were randomly selected for the study. Childs anxiety level was measured using three different scales namely (i) RMS-PS (ii) VPT, and (iii) FIS. Statistical Analysis: Student t test was used to compare the scores obtained from all the three scales. Pearson correlation test was used to obtain correlation among the scales used in the study. Results: A strong correlation (0·76) was found between the VPT and RMS-PS, and a moderate correlation (0.5) was found between RMS-PS and FIS, indicating good validity for the RMS-PS. Conclusions: The findings of this study suggest that the RMS-PS can be a newer and easiest means for the assessment of dental anxiety for young children in a clinical context.